2021
DOI: 10.1080/21505594.2021.1936432
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the immune response to Mycobacterium tuberculosis Beijing family infection: a perspective from the transcriptome

Abstract: Tuberculosis continues to be an important public health problem. Particularly considering Beijingfamily strains of Mycobacterium tuberculosis, which have been associated with drug-resistance and hypervirulence. The Beijing-like SIT190 (BL) is the most prevalent Beijing strain in Colombia. The pathogenic mechanism and immune response against this pathogen is unknown. Thus, we compared the course of pulmonary TB in BALB/c mice infected with Classical-Beijing strain 391 and BL strain 323. The disease course was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…In agreement with these results, the present study revealed that the Beijing genotype strain inhibited expression of IL-6, leading to induction of a relatively weak immune inflammatory response, consistent with the results of other studies [8, 22, 23]. Furthermore, mice infected with a Beijing genotype strain were shown in another study to exhibit overexpression of several cytokine genes associated with immune system suppression [24]. However, more recent studies have shown that the dominant subtype of genotype Beijing M.tb in China, the modern Beijing strain, can induce a stronger inflammatory response in host macrophages than other Beijing subtypes [25].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with these results, the present study revealed that the Beijing genotype strain inhibited expression of IL-6, leading to induction of a relatively weak immune inflammatory response, consistent with the results of other studies [8, 22, 23]. Furthermore, mice infected with a Beijing genotype strain were shown in another study to exhibit overexpression of several cytokine genes associated with immune system suppression [24]. However, more recent studies have shown that the dominant subtype of genotype Beijing M.tb in China, the modern Beijing strain, can induce a stronger inflammatory response in host macrophages than other Beijing subtypes [25].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the pink module, we identified several critical functional terms related to inflammation and immune response, such as “NF-kappa B signaling pathway,” “TNF signaling pathway,” and “B cell receptor signaling pathway” in the tan module, as well as terms such as “cytokine-mediated signaling pathway (GO:0019221),” “negative regulation of programmed cell death (GO:0043069),” “toll-like receptor 2 signaling pathway (GO:0034134),” and “negative regulation of epithelial cell apoptotic process (GO:1904036)” in the salmon module. Moreover, several hub-central genes/TFs of the tan module such as CD40 ( Khan et al, 2016 ), CD274 ( Petrilli et al, 2020 ), CTNNB1 ( Subuddhi et al, 2020 ), IKBKE ( Killick et al, 2014 ), IL23R ( Jiang et al, 2015 ), MAPK7 ( María Irene et al, 2021 ), TRAF2 ( Killick et al, 2014 ), NFKB1 ( Meade et al, 2007 ), NFKB2 ( Magee et al, 2012 ), and STAT6 ( Cronan et al, 2021 ), as well as hub-central genes of the salmon module, such as CASP4 ( Malone et al, 2018 ), DHX58 ( Nalpas et al, 2015 ), IL10 ( Wang et al, 2011 ), MX1 , MX2 , IFIT2 ( Yi et al, 2021 ), RIPK2 ( Widdison et al, 2011 ), TRAF1 ( Li H. et al, 2017 ), and USP18 ( Carranza et al, 2020 ), have been reported to be involved in the host immunity and M. bovis pathogenesis. The NFKB1 hub-central TF is a major mediator of the proinflammatory immune response that stimulates the transcription of proinflammatory cytokines and chemokines and has shown a significant reduction in the response to M. bovis infection ( Meade et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The occasional isolation of atypical Beijing mycobacteria from patients means that little is known about the effect of these pathogens on the course of treatment and prognosis. Only a few relevant reports have been published, including two from Colombia, describing cases of tuberculosis caused by the modern Beijing subtype 190 mycobacteria [ 38 , 39 ]. Another report described the case of a 15-year-old female patient infected with this subtype of multidrug-resistant MT who died after unsuccessful treatment [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…All strains isolated in 1992-1994 from this population of patients were characterized by the same pattern, RFLP-IS6110, with 15-20 copies of the insertion sequence and an atypical spoligotype compared to strains isolated in other regions of the world [10]. Isolates with such a DNA profile, cultured from patients in subsequent years, were defined as typical or classical Beijing, while clinical isolates containing only spacers [35][36][37][38][39][40][41][42][43] in the DR locus were named as atypical Beijing or Beijing-like [11]. Additional subdivision of the Beijing lineage is currently based on the presence of IS6110 insertions in the NTF chromosomal region and on the detection of alterations in putative mutator genes, mutT2 and mutT4.…”
Section: Introductionmentioning
confidence: 99%